Effectiveness of Japan’s Health Insurance System in Meeting Complex Long-Term Care Needs - Ryohei Yamamoto (Studies in Social Science & Humanities, 2024)
Japan’s Long-Term Care Insurance (LTCI) system, introduced in 2000, was designed to address the growing needs of the country’s aging population. This study evaluates the effectiveness of the LTCI system in meeting complex long-term care needs, focusing on four key dimensions: access, quality, financial sustainability, and user satisfaction. Using quantitative analysis of data from national databases and surveys, the study reveals significant improvements in access to services and positive care outcomes, with approximately 80% of beneficiaries expressing satisfaction with the services received. However, geographic disparities persist, with rural areas facing limited service availability compared to urban centers. Financial sustainability remains a critical concern, as expenditures have risen by 20% over the past five years, highlighting the need for innovative funding models. The study recommends policy interventions to address regional disparities, ensure financial viability, and expand specialized services for individuals with complex care needs. By examining these challenges and opportunities, the study provides insights into the strengths and limitations of the LTCI system and offers guidance for future policy development. The findings underscore the importance of targeted reforms to enhance the system’s capacity to deliver high-quality, equitable care to Japan’s elderly population.